Exchange-Rate Systems and Interest-Rate Behaviour: The Experience of Hong Kong and Singapore - TSE, Yiu Kuen (Institutional Knowledge at Singapore Management University, 2006)
The Currency Board System in Hong Kong and the monitoring band system in Singapore are important benchmarks for two different exchange-rate systems. In this paper we consider the implications of the two exchange-rate systems on the interest-rate behaviour of the two economies. We examine the domestic–US interest differentials under the two exchange-rate regimes during the Asian Financial Crisis as well as the pre-and post-crisis periods. Using a bivariate generalized autoregressive conditional heteroscedasticity model, we also investigate whether there is any change in the correlation between the domestic and US interest rates due to the Asian Financial Crisis.